2017
DOI: 10.1002/ange.201700580
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Observation of a Hydrogenated CO Dimer Intermediate During CO Reduction on Cu(100) Electrodes

Abstract: Carbon dioxide and carbon monoxide can be electrochemically reduced to useful products such as ethylene and ethanol on copper electrocatalysts. The process is yet to be optimized and the exact mechanism and the corresponding reaction intermediates are under debate or unknown. In particular, it has been hypothesized that the C−C bond formation proceeds via CO dimerization and further hydrogenation. Although computational support for this hypothesis exists, direct experimental evidence has been elusive. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
124
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 36 publications
5
124
0
Order By: Relevance
“…The formation of C 2 products is thought to first proceed through the formation of a CO dimer, followed by the formation of a surface‐bonded enediol or enediolate or the formation of an oxametallacycle . An in situ Fourier transform infrared (FTIR) spectroscopy experiment at low overpotentials in LiOH solutions indicated the presence of a hydrogenated dimer intermediate (OCCOH) that lends support to this hypothesis . Consequently, it seems that predicting how hydrocarbons are formed at Cu‐based electrodes is more complicated than simply using CO heat of adsorption (Figure ).…”
Section: Co2→c2 With Electrocatalytic Alloysmentioning
confidence: 78%
See 1 more Smart Citation
“…The formation of C 2 products is thought to first proceed through the formation of a CO dimer, followed by the formation of a surface‐bonded enediol or enediolate or the formation of an oxametallacycle . An in situ Fourier transform infrared (FTIR) spectroscopy experiment at low overpotentials in LiOH solutions indicated the presence of a hydrogenated dimer intermediate (OCCOH) that lends support to this hypothesis . Consequently, it seems that predicting how hydrocarbons are formed at Cu‐based electrodes is more complicated than simply using CO heat of adsorption (Figure ).…”
Section: Co2→c2 With Electrocatalytic Alloysmentioning
confidence: 78%
“…[24,54] An in situ Fourier transform infrared (FTIR) spectroscopy experiment at low overpotentials in LiOH solutionsi ndicated the presence of ah ydrogenatedd imeri ntermediate (OCCOH) that lends support to this hypothesis. [55] Consequently,i ts eems that predicting how hydrocarbons are formed atC u-based electrodes is more complicated than simply using CO heat of adsorption (Figure 1). Indeed, hydrocarbone volution studies have shown that even at iny fraction of secondary metalsc an be catastrophic to the hydrocarbon evolution ability of ac oppere lectrode.…”
Section: Co 2 !C 2 With Electrocatalytic Alloysmentioning
confidence: 99%
“…Thisc ould explain why practically no hydrocarbons and alcohols were detected, as their formation occurs through the hydrogenation/dimerization of CO* intermediates. [21,[34][35][36] The Cu-5000S catalyst exhibited the highest partial current density for formate at À0.9 VofÀ13.9 mA cm À2 ,w hich is approximately 8a nd 46 times higher than those of Cu-0S (j HCOO À = À1.8 mA cm À2 )and Cu(110) surfaces (j HCOO À = À0.3 mA cm À2 ), respectively,a tt he same potential. [21] At potentials negative to À0.9 V, the FE for formate production startedt od ecrease, and the FE for C 2 H 4 and ethanol production began to increase (5.5 and 2.0 %, respectively,a tÀ1.0 V).…”
Section: Resultsmentioning
confidence: 94%
“…The evolution of CO was minimal (FE CO =0.1–1.6 %) at all of the potentials studied. This could explain why practically no hydrocarbons and alcohols were detected, as their formation occurs through the hydrogenation/dimerization of CO* intermediates . The Cu‐5000S catalyst exhibited the highest partial current density for formate at −0.9 V of −13.9 mA cm −2 , which is approximately 8 and 46 times higher than those of Cu‐0S ( j HCOO- =−1.8 mA cm −2 ) and Cu(110) surfaces ( j HCOO- =−0.3 mA cm −2 ), respectively, at the same potential .…”
Section: Resultsmentioning
confidence: 99%
“…Pérez‐Gallent et al . have recently probed the C−C coupling process on Cu(100) surfaces and identified reaction intermediates using in situ FTIR spectroscopy . The electrochemical reduction of CO on Cu(100) was investigated at low overpotentials (+0.05 to −0.2 V vs. RHE) in 0.1 M LiOH.…”
Section: Analysis Of the Performance And Mechanisms Of Oxide‐derived mentioning
confidence: 99%